2015
DOI: 10.1179/2049396715y.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of household air pollution on child survival: evidence from demographic and health surveys in 47 countries

Abstract: Background: Over one-third of the world's population is exposed to household air pollution (HAP) but the separate effects of cooking with solid fuel and kerosene on childhood mortality are unclear. Objectives: To evaluate the effects of both solid fuels and kerosene on neonatal (0-28 days) and child (29 days-59 months) mortality. Methods: We used Demographic and Health Surveys from 47 countries and calculated adjusted relative risks (aRR) using Poisson regression models. Results: The aRR of neonatal and child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Data from a multicountry cohort study in India, Pakistan, Kenya, Zambia and Guatemala showed that the risks of neonatal mortality and macerated stillbirth were 80% and 66%, respectively, higher in households using polluting fuels such as kerosene, charcoal, coal, wood straw, crop waste and dung . Demographic and Health Survey (DHS) data in 47 countries revealed that neonatal mortality rates were 24% and child mortality rates 21% higher in households that used solid fuels for cooking . Similar evidence has been documented in Nigeria , India and Bangladesh .…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Data from a multicountry cohort study in India, Pakistan, Kenya, Zambia and Guatemala showed that the risks of neonatal mortality and macerated stillbirth were 80% and 66%, respectively, higher in households using polluting fuels such as kerosene, charcoal, coal, wood straw, crop waste and dung . Demographic and Health Survey (DHS) data in 47 countries revealed that neonatal mortality rates were 24% and child mortality rates 21% higher in households that used solid fuels for cooking . Similar evidence has been documented in Nigeria , India and Bangladesh .…”
Section: Introductionmentioning
confidence: 57%
“…Beyond the neonatal period, low birthweight is also a risk factor for post‐neonatal mortality and early onset of non‐communicable diseases in adulthood . These leading risk factors – preterm birth, pneumonia and low birthweight – have been shown to be associated with exposure to household air pollution from maternal smoking and use of solid fuel for cooking .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that children under the age of five compose the most susceptible group for fatalities caused by pollutant cooking fuels (Smith et al 2000;Gajate-Garrido 2013;Upadhyay et al 2015). Recent evidence in SSA also indicates that children under five are at a greater risk of death when solid fuel is used in the household (Ezeh et al 2014;Kleimola et al 2015). Nevertheless, the relationship between cooking fuel and risk of under-five mortality, on a much wider scale, has not been adequately determined in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have implicated HAP in respiratory tract cancers, respiratory infections and chronic lung diseases (4-8). Personal exposure assessment is necessary to understand the association between HAP and health outcomes (9-11) and define exposure response relationships (12); use of exposure proxies such as questionnaires may lead to substantial exposure misclassification.…”
Section: Introductionmentioning
confidence: 99%